Soft locality restrictions in negative concord: Evidence from the French future polarity effect - Liang, Yiming; Amsili, Pascal; Burnett, Heather (Natural language and linguistic theory, 2025)
This paper provides new evidence that syntactic principles that are proposed to explain the (un)grammaticality of a sentence can also hold in sociolinguistic variation. In particular, we argue that two puzzling frequency patterns involving negation in French—the proximity effect on negative concord and the polarity effect on future temporal reference—are deeply related and are both derived from the sensitivity of syntactic agreement to “soft” locality constraints. Recent quantitative studies of future temporal reference reveal that, although all negative items are subject to the polarity effect in Laurentian French, pas does not give rise to the polarity effect in Parisian French. We argue that this dialectal difference can be explained by minor variations in the syntactic and semantic properties of the negative marker pas , given an appropriate analysis of the syntax of negative concord. Our paper therefore shows that incorporating sociolinguistic variation into syntactic theory helps refine our understanding of general syntactic principles, such as locality constraints, and argues that frequency/preference patterns should be included in the full theory of syntactic competence and performance of speakers.